(untitled) (Research, Society and Development, 2024)
This study aimed to develop an effective technique for the vegetative propagation of Dipteryx ferrea (Ducke) Ducke (shihuahuaco), seeking to obtain quality plants in a shorter time, given that the species faces challenges due to limited access to seed trees. Juvenile cuttings of 5 to 7 cm were used, treated with three concentrations of Indole-3-Butyric Acid (IBA): 8000 ppm (control), 12000 ppm, and 18000 ppm. The cuttings were placed in tubes with four substrates: Jiffy (control), coconut fiber (CF), carbonized rice husk + chicken manure compost (CRH+CM), and carbonized rice husk + sawdust compost (CRH+SD), and then distributed in trays in a sub-irrigation chamber. The analysis of variance showed significant differences in rooting depending on the substrate, with CAC+G (90.28%), Jiffy (84.72%), CF (80.56%), and CAC+A (62.50%) standing out. The best concentration of IBA was 18000 ppm, achieving 95.80% rooting when combined with CAC+G. It is concluded that IBA and substrates have a positive effect on the propagation of Dipteryx ferrea in environments such as the sub-irrigation chamber and using tubes.